Acceptability and willingness to use HIV pre-exposure prophylaxis among HIV-negative men who have sex with men in Switzerland. (24th March 2016) - Gredig, Daniel; Uggowitzer, Franziska; Hassler, Benedikt; Weber, Patrick; Nideröst, Sibylle
ABSTRACT: Pre-exposure prophylaxis (PrEP) is discussed as an additional HIV prevention method targeting men who have sex with men (MSM). So far, PrEP has not been approved in Switzerland and only little is known about the acceptability of PrEP among MSM living in Switzerland. Given the slow uptake of PrEP among MSM in the USA, the objectives of the study were to investigate the acceptability for PrEP and to identify factors influencing the acceptability for this prevention method and the willingness to adopt it. During a 4-month period we conducted five focus group discussions with 23 consecutively sampled HIV-negative MSM aged 22–60 years living in Switzerland. We analyzed the data according to qualitative content analysis. The acceptability of PrEP varied considerably among the participants. Some would use PrEP immediately after its introduction in Switzerland because it provides an alternative to condoms which they are unable or unwilling to use. Others were more ambivalent towards PrEP but still considered it (1) an additional or alternative protection to regular condom use, (2) an option to engage in sexual activities with less worries and anxieties or (3) a protection during receptive anal intercourse independently of the sexual partner's protective behaviour. Some participants would not consider using PrEP at all: they do not see any benefit in PrEP as they have adopted safer sex practices and did not mention any problems with condom use. Others are still undecided and could imagine using an improved form of PrEP. The results provide a valuable basis for a model explaining the acceptability of PrEP among MSM and suggest including the personal HIV protection strategy in the considerations adopted.